Transient Expression of Secretory IgA In Planta is Optimal Using a Multi-Gene Vector and may be Further Enhanced by Improving Joining Chain Incorporation - Westerhof, Lotte B.; Wilbers, Ruud H. P.; van Raaij, Debbie R.; van Wijk, Christina Z.; Goverse, Aska; Bakker, Jaap; Schots, Arjen (Frontiers in Plant Science, 2016)
Secretory IgA (sIgA) is a crucial antibody in host defence at mucosal surfaces. It is a promising antibody isotype in a variety of therapeutic settings such as passive vaccination and treatment of inflammatory disorders. However, heterologous production of this heteromultimeric protein complex is still suboptimal. The challenge is the coordinate expression of the four required polypeptides; the alpha heavy chain, the light chain, the joining chain and part of the polymeric-Ig-receptor called the secretory component, in a 4:4:1:1 ratio. We evaluated the transient expression of three sIgAκ variants, harbouring the heavy chain isotype α1, α2m1 or α2m2, of the clinical antibody Ustekinumab in planta. Ustekinumab is directed against the p40 subunit that is shared by the pro-inflammatory cytokines interleukin (IL)-12 and IL-23. A sIgA variant of this antibody may enable localized treatment of inflammatory bowel disease. Of the three different sIgA variants we obtained the highest yield with sIgA1κ reaching up to 373 μg sIgA/ mg total soluble protein. The use of a multi-cassette vector containing all four expression cassettes was most efficient. However, not the expression strategy, but the incorporation of the joining chain turned out to be the limiting step for sIgA production. Our data demonstrate that transient expression in planta is suitable for the economic production of heteromultimeric protein complexes such as sIgA.